(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The problems of studying the concepts occupy an important cognitive niche in modern linguistics. The realization of conceptual integrity of a literary text mostly depends on correct interpretation of the concept itself and its links in a literary text. The questions related to the representation of the concept in a literary text written in a foreign language influence the process of representation an adequate world picture in the target text by the means of reconstruction of conceptual meanings involved in the conceptual sphere of the concept. The research demonstrates that conceptual links, as well as the zones of periphery, can be interpreted individually under the influence of author’s world picture. Therefore, in the process of preparation of the text to the translation it is recommended to conduct a conceptual analysis revealing individual-author’s connotations that influence the formation of implicit meanings realized through some certain knowledge structures.